Opting In and Opting Out: Bargaining for Fiduciary Duties in Cooperative Ventures - Jason Scott Johnston (Washington University Law Quarterly, 1992)
After surveying the Perfect-Markets analysis in Section I of this Article, Section II explores some strategic implications of its central insight regarding the imperfection of fiduciary duty protection. At the same time, by focusing just on strategic effects due to asymmetric information, the results in Section II are very limited and do not provide the backbone for a positive theory of opting in and opting out of fiduciary duties. Section III outlines how such a theory might proceed by considering a number of complicating factors that are important in the Perfect-Markets analysis and that also enrich the strategic approach in Section II. Section IV then applies my positive theory to selected doctrinal issues raised by the paradigm cases I described above.
Keywords: Fiduciary responsibility; Coase theorem; Close corporations